Altered long‐ and short‐range functional connectivity density associated with poor sleep quality in patients with chronic insomnia disorder: A resting‐state fMRI study. Issue 11 (16th September 2020) - Zhou, Fuqing; Zhu, Yanyan; Zhu, Yujun; Huang, Muhua; Jiang, Jian; He, Laichang; Huang, Suhua; Zeng, Xianjun; Gong, Honghan
Abstract: Introduction: Previous neuroimaging studies have suggested that brain functional impairment and hyperarousal occur during the daytime among patients with chronic insomnia disorder (CID); however, alterations to the brain's intrinsic functional architecture and their association with sleep quality have not yet been documented. Methods: In this study, our aim was to investigate the insomnia‐related alterations to the intrinsic connectome in patients with CID ( n  = 27) at resting state, with a data‐driven approach based on graph theory assessment and functional connectivity density (FCD), which can be interpreted as short‐range (intraregional) or long‐range (interregional) mapping. Results: Compared with healthy controls with good sleep, CID patients showed significantly decreased long‐range FCD in the dorsolateral prefrontal cortices and the putamen. These patients also showed decreased short‐range FCD in their multimodal‐processing regions, executive control network, and supplementary motor‐related areas. Furthermore, several regions showed increased short‐range FCD in patients with CID, implying hyper‐homogeneity of local activity. Conclusions: Together, these findings suggest that insufficient sleep during chronic insomnia widely affects cortical functional activities, including disrupted FCD and increased short‐range FCD, which is associated with poor sleep quality. Abstract : Using graph theory assessment and functional connectivity density (FCD) methods to investigate the insomnia‐related alterations to the intrinsic connectome in patients with CID patients, we found that insufficient sleep during chronic insomnia widely affects cortical functional activities, including disrupted FCD and increased short‐range FCD, which is associated with poor sleep quality.